1976
DOI: 10.1056/nejm197608192950804
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Glucose Regulation and Hemoglobin AIcin Diabetes Mellitus

Abstract: We studied the increased levels of hemoglobins AIa+Ib and AIc in five hospitalized diabetic patients to determine whether changes in diabetic control would cause parallel changes in the levels of these hemoglobins. Before control of diabetes the mean fasting blood sugar for all patients was 343 mg per deciliter (range, 280 to 450), and hemoglobin AIc concentration 9.8 per cent (range, 6.8 to 12.1). During optimal diabetic control the blood sugar concentration was 84 mg per deciliter (range, 70 to 100), and hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
555
1
12

Year Published

1979
1979
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,146 publications
(588 citation statements)
references
References 9 publications
20
555
1
12
Order By: Relevance
“…These showed that WA administration failed to reduce FBG levels but reduced HbA 1c levels in subjects after 2 and 3 months of treatment (Figure 4), and the effect was more apparent in subjects with higher initial HbA 1c levels (HbA 1c Z7.0) (Figure 5). Since HbA 1 c is an abnormally glycosylated hemoglobin (Bunn et al, 1976), which reflects overall blood glucose control (Koenig et al, 1976), the reductions of HbA 1 c might indicate that the long-term administration of WA improved the overall blood glucose control in diabetic patients with mild hyperglycemia. This was consistent with the suppression of postprandial hyperglycemia as shown in the single administration experiment.…”
Section: Discussionmentioning
confidence: 99%
“…These showed that WA administration failed to reduce FBG levels but reduced HbA 1c levels in subjects after 2 and 3 months of treatment (Figure 4), and the effect was more apparent in subjects with higher initial HbA 1c levels (HbA 1c Z7.0) (Figure 5). Since HbA 1 c is an abnormally glycosylated hemoglobin (Bunn et al, 1976), which reflects overall blood glucose control (Koenig et al, 1976), the reductions of HbA 1 c might indicate that the long-term administration of WA improved the overall blood glucose control in diabetic patients with mild hyperglycemia. This was consistent with the suppression of postprandial hyperglycemia as shown in the single administration experiment.…”
Section: Discussionmentioning
confidence: 99%
“…HbA1c is a time-averaged measure of blood glucose control and can be twice as high in patients with poor glucose control when compared to normal patients. 26 A total of 110 animals were used to measure cellular proliferation (n ¼ 26), histomorphometric (n ¼ 18), and biomechanical (n ¼ 66) parameters of fracture healing. All research protocols were approved by the Institutional Animal Care and Use Committee at the University of Medicine and Dentistry of New Jersey.…”
Section: Animal Modelmentioning
confidence: 99%
“…In addition, Ditzel et al [11] noted that Hb Aic values fell over a period of weeks to months following initiation of insulin therapy in a group of newly diagnosed diabetics. On the other hand, the rate of decline of Hb Aic values following imposition of rigorous diabetic control in a group of five diabetics described by Koenig et al [12] appeared inconsistent with a reduction in rate of synthesis alone. Furthermore, high correlations have been reported between Hb Aic values and virtually simultaneous blood glucose concentrations [13,14].…”
mentioning
confidence: 89%